COST EFFECTIVENESS OF BILATERAL SIMULTANEOUS VERSUS STAGED KNEE ARTHROPLASTIES - Iqbal, Malik Javed; Inam, Muhammad; Khan, Mumtaz (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the cost effectiveness of bilateral simultaneous knee arthroplasty in experienced hands. Material and Methods: This descriptive study was done in the Shotley Bridge General Hospital county Durham England from 2000-2003 on 26 patients undergoing bilateral simultaneous knee arthroplasty. Patients were randomized in two equal groups. Group A included 13 patients and had staged knee arthoplasty i.e. they had the same procedure in two hospital admissions under different anesthetic session. Group B comprised of 13 patients, underwent simultaneous knee arthroplasty. Same type of knee prosthesis was used in all cases and were operated by same surgeon in same institution. Results: In group A, 9 (69.2%) patients had osteoarthritis and 4 (30.8%) had rheumatoid arthritis while in group B twelve patients had osteoarthritis and one had rheumatoid arthritis. Only one patient had transient ischemic attack in group A while there was one case of deep vein thrombosis in group B. Average hospital stay for both groups was 15 days. The average cost for group A was Sterling £ 8950/- (Rs.1163500/-) and for group B was Sterling £ 5265/-(Rs.684450/-). Conclusion: This study shows that bilateral simultaneous arthroplasty is cost effective in experienced hands and do not have increased rate of complications.